Pengaruh Penggunaan Inoculant Cair Ragi Tape Dan Inoculant Cair Ragi Tempe Terhadap Waktu Pengomposan Sampah Organik Rumah Tangga Tahun 2010 - Zuanah Zuanah; Lucky Herawati; Sri Puji Ganefati (Sanitasi: Jurnal Kesehatan Lingkungan, 2011)
Improper handling of household organic wastes can causing serious problems on humans and the environment. One effort to solve the problem is by com-posting. However, since composting takes a long time, the processs needs materials as activator or inoculant to quicken the time needed. This study used liquid inoculant from tape yeast and tempe yeast at the same dose, to understand which one is the most effective. This research was an experiment with post test only with control group design. The organic wastes were taken from house-holds of Sukunan Village in Gamping and Ngabean Village in Pandak by following quota sampling method. The average time of composting in the control group was 53,8 days, while in the treatment group 1 was 19,93 days (33,93 days faster compared with the control) and in the treatment group 2 was 23,67 days (30,13 days faster compared with the control). The com-posting time data were analyzed by using Kruskal-Wallis test at 0,05 significance level; and gained p-value <0,001, which means the difference composting times among groups were significant. The subsequent Mann-Whitney test obtained p-values<0,001 for all pairs comparing, therefore it can be concluded that tape yeast liquid inoculant is more effective than the tempe one in accelerating the composting time.